Incidencia de la estimulación temprana en el desarrollo afectivo, cognititvo y psicomotriz en niños y niñas con síndrome de down de 0-10 años, en el instituto de Educación Especial El Oro, de la Ciudad de Machala durante el período 2011-2012. - Capa Maza, María Elizabeth (2012)
Pacing in this regard is interested in the affective, cognitive and psychomotor area achieving equal opportunities, it has been found that the formation of habits, positive today and a stimulating home environment are part of a good development.